2013
DOI: 10.1080/02640414.2012.736634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a shoot training programme with a reduced hoop diameter rim on free-throw performance and kinematics in young basketball players

Abstract: The present paper investigated the effects of a shoot training programme with a reduced hoop diameter (0.35 m) rim on kinematics and performance of basketball free-throws. Eighteen young male basketball players were divided into control (CG, n = 9) and experimental (EG, n = 9) groups. Both groups undertook a 10-week training programme comprising two training sessions per week. Under fatigued conditions, each participant shot 150 free-throws in each training session, with the CG using a standard rim, and the EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Especially when fine motor control is involved, a necessary second step involves optimizing the execution of each element in the sequence (Penhune and Steele, 2012). Movement timing and movement velocity are two aspects of skilled motor performance that PP has been shown to optimize (e.g., Sanders, 1999; Khlifa et al, 2013). A surprisingly small number of studies has investigated whether this is the case for MP also, as most investigations have been concerned with practice outcome alone.…”
Section: Discussionmentioning
confidence: 99%
“…Especially when fine motor control is involved, a necessary second step involves optimizing the execution of each element in the sequence (Penhune and Steele, 2012). Movement timing and movement velocity are two aspects of skilled motor performance that PP has been shown to optimize (e.g., Sanders, 1999; Khlifa et al, 2013). A surprisingly small number of studies has investigated whether this is the case for MP also, as most investigations have been concerned with practice outcome alone.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the kinematics of the shoulder were associated with the accuracy of the free throw. Khlifa and colleagues 16) investigated the effects of a shoot training program with a reduced hoop diameter rim on the kinematics and performance of basketball free throws. The shoulder angle at ball release increased with shoot training, whereas the kinematics of the knee and ankle remained unchanged.…”
Section: Kinematic Datamentioning
confidence: 99%
“…The free-throw shoot differs from other shots, such as 2-point, 3-point, and jumping shots, because players can take more time (five seconds), and can shoot with no pressure from opponent players. Many studies have reported factors affecting the accuracy of the free-throw, such as grip strength 1) , the pre-shot routine [2][3][4][5] , ball trajectory [6][7] , back spin 8) , quiet eye [9][10] , heart rate 11) , height of the release ratio, the center of gravity 12) , brain activity 13) , sleep time 14) , wrist-joint position sense 15) , kinematics of the shoulder angle 16) , elbow-wrist coupling 17) , and the kinematic chain 18) . However, these studies each focused on a singular factor at a time rather than multiple factors simultaneously in their effects on free-throw accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of a projectile landing on or near a target – also known as endpoint accuracy – can determine success in many sports . For example, in darts the impact location of the dart on the target determines the points that are scored, in hoop‐based sports such as netball and basketball the ball must fall through the hoop, and in goal‐based sports such as soccer and hockey the ball must land within the defined area captured by a net …”
Section: Introductionmentioning
confidence: 99%